2011
DOI: 10.1097/meg.0b013e328347322b
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B in the southeast of China

Abstract: Borderline intermediate/high endemicity was found among adults in the northern region of Zhejiang Province. The vaccination program has contributed to a reduction in infection over the last 20 years, although further efforts are required to turn the region into a 'low-endemicity' area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 20 publications
2
21
1
Order By: Relevance
“…However, it is likely that the findings are related to differences in lifestyle or behaviors among males and females, such as smoking, drinking, extensive social range, physical activity, dining out, hygiene, and sexual activity. Luo et al and Tsai et al reported that inhabitants of the plain regions had lower rates of infection than those living in island regions (7, 19). However, differences in HBeAg positivity among regions have remained unknown.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it is likely that the findings are related to differences in lifestyle or behaviors among males and females, such as smoking, drinking, extensive social range, physical activity, dining out, hygiene, and sexual activity. Luo et al and Tsai et al reported that inhabitants of the plain regions had lower rates of infection than those living in island regions (7, 19). However, differences in HBeAg positivity among regions have remained unknown.…”
Section: Discussionmentioning
confidence: 97%
“…In the Zhejiang Province, the EPI vaccination program is considered a success. Since the initiation of the program in 1992, high-risk hepatitis B designation has moved from infants and children (0-9 years old) and adults (30-39 years old) to middle-aged adults (40-49 years old) (7, 8). In the current study, the constituent ratio was the highest among 40-49 year-olds and the lowest among < 20 year-olds, further confirming the former epidemiological discovery.…”
Section: Discussionmentioning
confidence: 99%
“…About 600000 people die every year due to the acute or chronic consequences of hepatitis B [1]. The prevalence in China is high and includes an estimated 120 million asymptomatic carriers and 6.9 million people infected with HBV, with a prevalence as high as 7.9% [2,3]. Chronic hepatitis B (CHB) increased the risk of liver failure and hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, it is estimated that more than 2 billion people have been infected with Hepatitis B virus (HBV), one-third reside in China [1]. Over the last 20 years, although the vaccination program has contributed to a reduction in HBV infection, decreasing from nearly 10% to approximately 7% in the general population [2], China is still an intermediate/high endemic country for hepatitis [3,4]. …”
Section: Introductionmentioning
confidence: 99%